The Principal Leadership in Improving Teacher Performance - Abdul Wahid (Yayasan Avicenna, 2022)
This study describes the Principal's leadership in improving teacher performance at MTs Nurul Qadim Paiton. The background of this study stems from the central role of the principal as an educational leader in creating a conducive school environment that supports the professional development of teachers. In many Islamic education institutions, teacher performance is often influenced by the leadership approach implemented by the school principal. Therefore, understanding the leadership style that effectively enhances teacher performance is crucial to achieving quality education. The objective of this research is to analyze how the principal's leadership strategies influence teacher motivation, discipline, and instructional effectiveness at MTs Nurul Qadim. This research uses a descriptive qualitative approach with a case study research design to gain in-depth insight. The subjects in this study were the principal and several teachers who were selected using purposive sampling. Data were collected through observation, semi-structured interviews, and document studies, ensuring triangulation as a technique for data validity. Data were analyzed using Miles and Huberman's model, which includes data reduction, data display, and conclusion drawing. The results of the study reveal that the principal employs a dual approach: task-oriented and relationship-oriented leadership. The task-oriented behavior is demonstrated through structured supervision, the implementation of sanctions for violations, and the provision of performance-based rewards. Meanwhile, the relationship-oriented behavior is reflected in the principal's exemplary conduct, personal attention and emotional support to teachers, as well as the facilitation of ongoing professional development through training programs. These leadership practices significantly contribute to improving teacher performance, morale, and work commitment.